2012
DOI: 10.1177/0959651812450114
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent tapping control

Abstract: Control using a sequence of ‘taps’, in contrast to the usual smooth control, is shown to fit within the established intermittent control framework. In particular, a specially designed generalised hold gives rise to tapping behaviour optimised according to the underlying linear-quadratic design. Both fixed-interval and event-driven tapping are included in this approach and some basic stability analysis is given. Illustrative examples are presented and the advantages of tapping in the context of electromechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Evidence from sustained manual control of an external single degree of freedom system (Loram et al, 2012; van de Kamp et al, 2013) showed that it is unlikely that the entire sensory-motor pipeline is implemented in parallel as a continuous linear time invariant process. Rather the evidence is highly consistent with a limiting serial process along a single channel which is expressed formally in the intermittent control paradigm illustrated in Figure 1 (Gawthrop and Wang, 2011; Gawthrop et al, 2011; Gawthrop and Gollee, 2012; Loram et al, 2012). The hypothesis of a limiting serial, single channel process is supported by extensive studies in Psychology showing refractoriness in double stimulus experiments.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Evidence from sustained manual control of an external single degree of freedom system (Loram et al, 2012; van de Kamp et al, 2013) showed that it is unlikely that the entire sensory-motor pipeline is implemented in parallel as a continuous linear time invariant process. Rather the evidence is highly consistent with a limiting serial process along a single channel which is expressed formally in the intermittent control paradigm illustrated in Figure 1 (Gawthrop and Wang, 2011; Gawthrop et al, 2011; Gawthrop and Gollee, 2012; Loram et al, 2012). The hypothesis of a limiting serial, single channel process is supported by extensive studies in Psychology showing refractoriness in double stimulus experiments.…”
Section: Introductionsupporting
confidence: 60%
“…If RT2 were linearly related to ISI with a gradient of −1, then as clearly articulated by Pashler and Johnston (1998) that would be consistent with a serial process along a single channel in which a second process cannot start until a first process has completed. Within a control system, this idea is represented within an intermittent control paradigm in which feedback cannot be applied until a minimum open loop interval has elapsed (Figure 1) (Gawthrop and Wang, 2009, 2011; Gawthrop et al, 2011; Gawthrop and Gollee, 2012; Loram et al, 2012). The minimum open loop interval, or intermittent interval as it is called, is an implementation of the single channel PRP as expressed by Craik (Vince, 1948) and Pashler (Pashler et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The hold state h replaces the predictor state p in the controller equation. Other holds (where A h ~= A c ) are possible [27]. Figure 1.…”
Section: Controlmentioning
confidence: 99%
“…These system parameters will be estimated in order to update the corresponding controller in the redesign stage. For this system, the statevector is defined in equation (47), which needs to be augmented by the system parameters to obtain the form given by equation (24). The arm and pendulum angles are the outputs of the system and can be defined in vector form as y(t) = ½ u a T .…”
Section: Augmented Rotational Pendulum Model For Parameter Estimationmentioning
confidence: 99%
“…Alternative versions are also possible, such as the tapping hold. 24 At the start of each intermittent interval, t = t i , the hold states are reset to the predicted state…”
Section: The System-matched Holdmentioning
confidence: 99%